BodyMap: A Collection of 3′ ESTs for Analysis of Human Gene Expression Information - Kawamoto, Shoko; Yoshii, Junji; Mizuno, Katsuya; Ito, Kouichi; Miyamoto, Yasuhide; Ohnishi, Tadashi; Matoba, Ryo; Hori, Naohiro; Matsumoto, Yuhiko; Okumura, Toshiyuki; Nakao, Yuko; Yoshii, Hisae; et al.

(untitled) (Genome Research, 2000)
BodyMap is a collection of site-directed 3′ expressed sequence tags (ESTs) (gene signatures, GSs) that contains the transcript compositions of various human tissues and was the first systematic effort to acquire gene expression data. For the construction of BodyMap, cDNA libraries were made, preserving abundance information and histologic resolutions of tissue mRNAs. By sequencing 164,000 randomly selected clones, 88,587 GSs that represent chromosomally coded transcripts have been collected from 51 human organs and tissues. They were clustered into 18,722 independent 3′ termini from transcripts, and more than 3000 of these were not found among ESTs assembled in UniGene (Build 75). Assessment of the prevalence of polyadenylation signals and comparison with GenBank cDNAs indicated that there was no significant contamination by internally primed cDNAs or genomic fragments but that there was a relatively high incidence (12%) of alternative polyadenylation sites. We evaluated the sensitivity and resolution of expression information in BodyMap by in silico Northern hybridization and selection of tissue-specific gene probes. BodyMap is a unique resource for estimation of the absolute abundance of transcripts and selection of gene probes for efficient hybridization-based gene expression profiling. [BodyMap data are available at http://bodymap.ims.u-tokyo.ac.jp.]